2013
DOI: 10.1111/mec.12419
|View full text |Cite
|
Sign up to set email alerts
|

High connectivity across the fragmented chemosynthetic ecosystems of the deepAtlanticEquatorialBelt: efficient dispersal mechanisms or questionable endemism?

Abstract: Chemosynthetic ecosystems are distributed worldwide in fragmented habitats harbouring seemingly highly specialized communities. Yet, shared taxa have been reported from highly distant chemosynthetic communities. These habitats are distributed in distinct biogeographical regions, one of these being the so-called Atlantic Equatorial Belt (AEB). Here, we combined genetic data (COI) from several taxa to assess the possible existence of cryptic or synonymous species and to detect the possible occurrence of contempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 100 publications
4
67
2
Order By: Relevance
“…Sampling is also an issue for species described as geographically restricted or ecologically specialized: sampling the targeted species and closely related taxa in other localities or habitats may help rejecting hypotheses of endemism and/or specialization. For example, recent molecular analyses revealed that chemosynthetic shrimp that were considered as distinct in cold seeps and hot vents actually corresponded to a single species with high gene flow across the Atlantic (Box 3; Teixeira et al 2013). A similar case was reported in a deep-sea mussel (genus Idas Jeffreys, 1876), where specimens sampled in a deep cold seep site and on vertebrate bones were previously falsely attributed to distinct species (Ritt et al 2012;Thubaut et al 2013).…”
Section: T a X O N O M I C F O U N D A T I O N S O F C O N N E C T I mentioning
confidence: 92%
“…Sampling is also an issue for species described as geographically restricted or ecologically specialized: sampling the targeted species and closely related taxa in other localities or habitats may help rejecting hypotheses of endemism and/or specialization. For example, recent molecular analyses revealed that chemosynthetic shrimp that were considered as distinct in cold seeps and hot vents actually corresponded to a single species with high gene flow across the Atlantic (Box 3; Teixeira et al 2013). A similar case was reported in a deep-sea mussel (genus Idas Jeffreys, 1876), where specimens sampled in a deep cold seep site and on vertebrate bones were previously falsely attributed to distinct species (Ritt et al 2012;Thubaut et al 2013).…”
Section: T a X O N O M I C F O U N D A T I O N S O F C O N N E C T I mentioning
confidence: 92%
“…longirostris showed no genetic differentiation among 3 vent sites in the Okinawa Trough (Hatoma Knoll, Izena Hole, and Irabu Knoll) and a seep site in Sagami Bay (the Off Hatsushima site). Similarly, no genetic differentiation was detected between local populations of alvinocaridids at seep sites in the Gulf of Mexico and West Africa, and the Logatchev vent field (Teixeira et al 2013). These results indicate that differences between vent and seep environments are not primary factors in determining the geographical distribution and genetic population structure of certain alvinocaridids.…”
Section: Genetic Population Structurementioning
confidence: 92%
“…Two species of Rimicaris shrimp, R. exoculata and R. kairei, also exhibit high haplotype diversity (0.69 to 0.89) in all local populations within their wide distributional range on the MAR and CIR, respectively (Teixeira et al 2011, Beedessee et al 2013. Moreover, a pair of synonymous species, A. muricola/markensis, which were suggested to exhibit connectivity across the Gulf of Mexico, the MAR, and West Africa, exhibit quite high haplotype diversity in each local population (0.80 to 0.91; Teixeira et al 2013). Populations of an undescribed Chorocaris shrimp, which are distributed in both the Manus and North Fiji basins in the SWP, also exhibit high haplotype diversity (0.70 to 1.00; Thaler et al 2014).…”
Section: Genetic Diversity and Population Expansionmentioning
confidence: 99%
“…For example, Young et al (2008) found a general southward pattern of migration along the northeast Pacific system, and larger effective population sizes of the siboglinid tubeworm Ridgeia piscesae in the southern populations compared to those in the north. Coalescent approaches have also been implemented to measure long-term migration rates in mollusk and polychaete species along the EPR (Plouviez et al, 2009(Plouviez et al, , 2010(Plouviez et al, , 2013, crustacean and mollusk species in the Indian Ocean ridges (Thaler et al, 2011;Beedessee et al, 2013;Chen et al, 2015), alvinocaridid shrimp from the MidCayman Spreading Center (Plouviez et al, 2015) and the Mid-Atlantic Ridge (Teixeira et al, 2012(Teixeira et al, , 2013. Despite the evident advantages of coalescent approaches over traditional Fstatistics, the migration estimates obtained through many of these approaches are considered long-term because of necessary equilibrium assumptions over the last ∼4N e generations (i.e., average time to coalescence).…”
Section: Genetic Approaches To Metacommunity Dynamics On Ecological Tmentioning
confidence: 99%